ALAT KEAMANAN PINTU BRANKAS BERBASIS SENSOR SIDIK JARI DAN PASSOWORD DIGITAL DENGAN MENGGUNAKAN MIKROKONTROLER ATMEGA 16 - Eni Yuliza; Toibah Umi Kalsum (UNIVED Press, 2015)
Doors safety deposit box still use conventional security. Where the safety deposit box door is opened by turning around and use the code, which in a sense it is not efficient. Therefore, the necessary measures to facilitate the safety deposit box door security. The purpose of this research is to create a security system safety deposit box door using fingerprint sensor R305 series. Other major equipment includes a microcontroller ATMega 16 and Visual Basic 6.0. The results showed that the Safe Door Security Tools can be monitored using applications created with Visual Basic 6.0 in accordance with the instructions given. The test results showed that the response to the command of instrument of the application is running normally. The success of the test results instrument is 100%.Keyword: Mikrokontroler AVR ATMEGA16, Visual Ianguage Pemrograman Basic 6.0, Appliance Security Door, Brankas Sensor Fingerprint and Digital Password